Experience of controlling behaviour and intimate partner violence among women of reproductive age in sub-Saharan Africa - Richard Gyan Aboagye; King David Dzirasah; Mainprice Akuoko Essuman; Qorinah Estiningtyas Sakilah Adnani; Bright Opoku Ahinkorah (BMC Women's Health)
Abstract Background Sub-Saharan Africa is noted for its high prevalence of intimate partner violence (IPV), affecting approximately 33% of women over their lifetime. However, little research has focused on the association between women’s experience of controlling behaviour and IPV. This study investigates the controlling behaviours exhibited by partners and their association with IPV among women in sub-Saharan Africa. Methods We performed a cross-sectional analysis of secondary data obtained from nineteen Demographic and Health Surveys in sub-Saharan Africa conducted from 2015 to 2021, using a weighted sample of 85,166 women in sexual unions. Multivariate logistic regression analyses were used to examine the association between controlling behaviour and past-year experience of IPV against women. Results The pooled prevalence of physical violence, emotional violence, sexual violence, and any IPV was 18.0% (17.5–18.5), 24.3% (23.8–24.9), 8.9% (8.6–9.2), and 32.1% (31.5–32.6), respectively. Regarding partner controlling behaviour, the prevalence of low, moderate, and high levels was 42.1%, 29.0%, and 28.9%, respectively. The odds of experiencing physical violence were higher among women who experienced medium [adjusted odds ratio (aOR) = 2.31; 95% confidence interval (CI) = 2.13–2.51] and high [aOR = 5.45; 95% CI = 5.04–5.89] levels of controlling behaviour. Also, women who experienced medium [aOR = 2.90; 95% CI = 2.70–3.11] and high [aOR = 6.96; 95% CI = 6.49-7.46] levels of controlling behaviour had higher odds of experiencing emotional violence compared to those who encountered low controlling behaviour. Similarly, women who experienced medium [aOR = 2.00; 95% CI = 1.81–2.22] and high [aOR = 5.01; 95% CI = 4.58–5.47] partner controlling behaviour had higher odds of sexual violence relative to those who were subjected to low controlling behaviour. Additionally, the likelihood of experiencing any IPV was higher among women who were subjected to medium [aOR = 2.61; 95% CI = 2.46–2.78] and high [aOR = 6.20; 95% CI = 5.82–6.60] levels of controlling behaviours relative to those who encountered low controlling behaviours. Conclusion Our study has shown that women’s experience of an act or form of controlling behaviour is associated with their subsequent experience of IPV. To reduce IPV among women in sub-Saharan Africa, policymakers and stakeholders must implement proactive measures that address various forms of controlling behaviours. Women and girls should be empowered to recognize and respond to any form of controlling behaviour in their intimate relationships, as it may later influence their experience of IPV. Existing policies and legislation on IPV should include and prioritise coercive controls as forms of abuse within relationships. Additionally, acts demonstrating controlling behaviours should be incorporated into IPV screening tools to help identify those at risk of experiencing coercive controls.